HUBUNGAN ANTARA KECERDASAN INTELEKTUAL (IQ) DENGAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN - Aliza Alfionita; Ujang Jamaludin; Dinar Sugiana Fitrayadi (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2019)
This study aims to find out the relationship between Intellectual Intelligence and Student Learning Citizenship Education Lessons. The research method of this research is a quantitative correlation approach. Samples were taken by Proposal Random Sampling technique, which was 72 samples. The instruments used in this study were Intelligence Tests and used Achievement Tests and observations as supporting data. While the data analysis used Simple Linear Regression with intellectual intelligence (x) as a predictor and learning achievement of Citizenship Education (Y). by komasiasi obtained the following correlation coefficient of 0.716 means (0,513 x 100%) = 51.3%. Learning Achievement Citizenship Education is influenced by intellectual intelligence while the remaining 48.7% is determined by other variables which are not examined in this study. Based on the results of the study, it can be concluded that Intellectual Intelligence has a Significant Relationship with Student Achievement in Citizenship Education.